2021
DOI: 10.37382/jomts.v3i1.467
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la funcionalidad del miembro superior en personas adultas con daño cerebral adquirido realizada por los/as profesionales de la terapia ocupacional en España, estudio transversal

Abstract: Introducción: La evaluación de las actividades y la participación son dos elementos claves en la funcionalidad del miembro superior (MS) para el proceso de neurorrehabilitación. Conocer la evaluación que realizan los/as profesionales de la terapia ocupacional puede ser de utilidad para la rehabilitación. Por tanto, el objetivo principal del estudio fue describir el proceso de evaluación del MS en adultos con daño cerebral adquirido (DCA), realizado por terapeutas ocupacionales en España. Métodos: Se dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…The most commonly used content validation processes involve the assessment of the items of the scale by a panel of experts; however, the instrument in this study is widely used in clinical practice, which would imply that it has the support of professionals, in addition to being recommended by CAULIN [ 12 ] and SRRR [ 13 ]. In addition, it is an instrument of which the translation into Spanish has been used in other studies [ 17 , 21 , 23 , 24 , 44 , 45 ], so it is considered that this content validity process has already been performed for this version of the tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used content validation processes involve the assessment of the items of the scale by a panel of experts; however, the instrument in this study is widely used in clinical practice, which would imply that it has the support of professionals, in addition to being recommended by CAULIN [ 12 ] and SRRR [ 13 ]. In addition, it is an instrument of which the translation into Spanish has been used in other studies [ 17 , 21 , 23 , 24 , 44 , 45 ], so it is considered that this content validity process has already been performed for this version of the tool.…”
Section: Discussionmentioning
confidence: 99%
“…The ARAT measure has been validated in several countries [ 17 , 19 , 20 , 21 , 22 , 23 ] and translated into Spanish; however, it has been adapted only to the Hispanic American population [ 17 , 22 ]. However, some studies conducted in Spain [ 24 , 25 ] have used the version of the scale translated into Spanish, but without validation for this population.…”
Section: Introductionmentioning
confidence: 99%
“…In recent Delphi studies about assessment tools for the stroke population, occupational therapists were underrepresented compared with other health professions (Kwakkel et al, 2017; Pohl et al, 2020). Cuesta-García et al (2021) explored the UL assessment process of Spanish occupational therapists in adults with acquired brain injury (ABI). They identified 110 assessment tools and found that most occupational therapists mainly assessed the body functions and structures component of the ICF (Cuesta-García et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cuesta-García et al (2021) explored the UL assessment process of Spanish occupational therapists in adults with acquired brain injury (ABI). They identified 110 assessment tools and found that most occupational therapists mainly assessed the body functions and structures component of the ICF (Cuesta-García et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…People suffering from neurological conditions endure situations in their daily lives that cause severe disability and restrict participation in meaningful activities (Cuesta-García and Alegre-Ayala, 2022; Josman et al, 2020). Occupational performance is a holistic and integrated way of life that a person defines as valuable and relevant, so occupational performance is achieved through active participation in carrying out routines, roles, tasks, and subtasks in his/her own integration of self-care, leisure, and productivity (Blain and Townsend, 1993; Nott et al, 2021).…”
Section: Introductionmentioning
confidence: 99%